Buck converter switching design using microcontroller - Che Sham, Izwan (2013)
This paper presents an implementation of a PIC18F4550 microcontroller to control the operation of a buck converter. Buck converter is a DC-DC converter which will step down a higher voltage to a lower voltage level. This microcontroller is used to produce Pulse Width Modulation (PWM) signal with constant duty cycle to drive the switch of the converter. The switch then will alternate turn the converter on and off to produce regulated voltage. The buck converter was modeled and evaluated by computer simulations. The author also present the simulation results related to the theoretical aspects mentioned in the paper. The result shows that the proposed PIC18F4550 microcontroller operation is capable to control the operation of the buck converter.